Sensory characterization of Baijiu pungency by combined time-intensity (TI) and temporal dominance of sensations (TDS). (September 2021) - He, Yingxia; Chen, Shuang; Tang, Ke; Qian, Michael; Yu, Xiaowei; Xu, Yan
Graphical abstract: Highlights: The temporal perception of pungency of Baijiu were evaluated by TI and TDS. Baijiu with different aging times differed in their temporal profiles of pungency. Pungency differences of Baijiu were related to both intensity and sub-qualities. TI and TDS supplied more valuable information of temporal differences, which were not identified using static methods. Abstract: Pungency is increasingly being recognized as an important factor of overall sensory quality, palatability, and consumer preference of distilled spirits. The characterization of pungency is necessary to evaluate the potential sensory quality of distilled spirits. In this study, the temporal profiles of pungency of Baijiu with different aging times were evaluated using time-intensity (TI) and temporal dominance of sensations (TDS) methods, considering both pungency intensity and pungency sub-qualities. TI results indicated significant differences in release rate of pungency during Baijiu consumption. Compared to young Baijiu, old Baijiu tend to show higher release rate of pungency, the areas under the curve and duration of pungency were significantly decreased in old Baijiu. The TDS results showed significant differences in the combination of dominant sub-qualities, as well as in the maximum dominance rates and the dominant duration of sub-qualities among Baijiu. The young Baijiu were mainly characterized by the dominant sub-qualities of "burning" and "numbing", whereas for old Baijiu, "burning", "prickle", and "drying" were dominant. The application of TI and TDS provided dynamic and temporal profiles of pungency to fully characterize pungency differences of distilled beverages.